PENGARUH PEMBELAJARAN E- LEARNING / ONLINE TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN EKONOMI TINGKAT II UNIVERSITAS NUSANTARA PGRI KEDIRI SELAMA PANDEMI COVID’19 - R, Wita Nur; W S, Thalita Yumna; Fortunilla, Aini; Prastyaningtyas, Efa Wahyu (Universitas Nusantara PGRI Kediri, 2020)
The existence of COVID-19 currently has an impact on the education system in Indonesia. The result of the decision from the minister of education that all learning activities both in schools and colleges are carried out in their respective homes through the available application. The Minister of Education issued Circular Number 3 Year 2O2O concerning the Prevention of Corona Virus Disease (COVID-l9) in the Education Unit which stated that schools and colleges were closed. This is done to break the chain of spreading COVID-19, instead learning activities are carried out online for all levels of education. Therefore we conducted research on the effect of online / online learning on student learning outcomes. This type of research uses a questionnaire that will be filled in by students. The population in this study were all students of the 2nd level of Economics Education Study Program, Nusantara University PGRI Kediri. Student learning outcomes data obtained from the results of filling out a questionnaire / questionnaire after treatment, the data is then processed by validity test, reliability test, normality test, linearity test and regression test. The results showed that there was a strong influence on online / online learning on the learning outcomes of students of the 2nd level of Economics Education Study Program, Universitas Nusantara PGRI Kediri during the covid'19 pandemic.